Did Trichromatic Color Vision and Red Hair Color Coevolve in Primates?. Issue 7 (28th November 2012) - KAMILAR, JASON M.; HEESY, CHRISTOPHER P.; BRADLEY, BRENDA J.; Higham, James P.; Semple, Stuart
<x xml:space="preserve">Abstract</x> Reddish pelage and red hair ornaments have evolved many times, independently, during primate evolution. It is generally assumed that these red‐coat phenotypes, like red skin phenotypes, play a role in sociosexual signaling and, thus evolved in tandem with conspecific color vision. This study examines the phylogenetic distribution of color vision and pelage coloration across the primate order to ask: (1) did red pelage and trichromacy coevolve; or (2) did trichromacy evolve first, and then subsequently red pelage evolved as an exaptation? We collected quantitative, color‐corrected photographic color data for 142 museum research skins from 92 species representing 41 genera spanning all major primate lineages. For each species, we quantified the ratio of Red/Green values (from a RGB color model) at 20 anatomical landmarks. For these same species, we compiled data on color vision type (routine trichromatic, polymorphic, routine dichromatic, monochromatic) and data on variables that potentially covary with visual system (VS) and coloration, including activity pattern and body mass dimorphism (proxy for sexual selection). We also considered whether the long‐term storage of research skins might influence coloration. Therefore, we included the time since the specimen was collected as an additional predictor. Analyzing the data with phylogenetic generalized least squares models, we found that the amount of red hair present in primates is associated with differences in VSs, but not in the direction expected. Surprisingly, trichromatic primate species generally exhibited less red hair compared to red‐green colorblind species. Thus, our results do not support the general assumption that color vision and red pelage coloration are a coevolutionary product of sociosexual signaling in primates. In addition, we did not find an effect of activity pattern, body mass dimorphism, or time since collection on the redness of primate hair. Our results have important implications for the evolution of primate coloration and visual systems. Am. J. Primatol. 75:740‐751, 2013. © 2012 Wiley Periodicals, Inc.